Some Aspects of Treatment Tactics for Fractures of Long Bones of The Lower Extremities (Eurasian Medical Research Periodical, 2024)
The work analyzed the treatment of 98 patients with polytrauma severity ≥16 points according to R-AIS-NISS, which included open III (A, B, C) type according to GustiloAndersen and closed multiple fractures of the long bones of the lower extremities, which were divided into 3 groups depending on the applied algorithm for providing medical care. The mortality rate and the number of infectious complications were studied when using 3 medical care algorithms for injury severity ≥16 points according to R-AIS-NISS. The result of the analysis was the development of an algorithm for providing medical care, the implementation of which made it possible to reduce the mortality rate and the number of infectious complications in patients with polytrauma, part of which were open type III (A, B, C) and closed multiple fractures of the long bones of the lower extremities.